Suprapatellar plica classification and suprapatellar plica syndrome - Machiko Akao; Tatsunori Ikemoto; Takuya Takata; Kazumasa Kitamoto; Masataka Deie (Elsevier, 2019)
Background: Plicae around the knee are anatomically normal structures that are remnants of embryonic membranes and are generally asymptomatic. Synovial plica syndrome is known to cause knee symptoms; however, its pathological contribution has been rarely reported. This study aimed to investigate the clinical significance of suprapatellar plicae as well as the morphological characteristics of suprapatellar plicae in patients with knee symptoms who required arthroscopic treatment. Methods: Of 223 arthroscopic knee surgeries, 125 patients undergoing primary arthroscopy for various diseases were eligible for inclusion in this study. All affected knees were preoperatively examined by two skilled physicians in a routine manner. Each patient was diagnosed with one primary disease entity based on clinical examinations and arthroscopic findings. At least two skilled orthopedic physicians watched the surgical videos together and defined the type of plicae based on the Dandy classification (Dandy DJ. 1990) as follows: (A) absent, (B) the plica was up to one-quarter of the width of the suprapatellar pouch, (C) the plica was between one-quarter and one-third of the width of the suprapatellar pouch, (D) the plica was between one-third and two-thirds of the width of the suprapatellar pouch, (E) the plica was more than two-thirds of the width of the suprapatellar pouch, (F) the plica had a complete membrane, (G) the plica was perforated, (H) arch, (I) pillar, or (J) lateral. Suprapatellar plica syndrome was considered when (1) the patient complained of anterior knee pain and had localized tenderness above the suprapatellar pouch, (2) magnetic resonance imaging revealed suprapatellar plica structures, and (3) other suspicious pathologies accounting for knee symptoms were excluded. We investigated primary disease type, type of plica, and the relationships between them. Results: The results revealed that meniscus injuries and anterior cruciate ligament injuries caused the majority of primary diseases (approximately 80%). Regarding plica forms, 23 knees were classified as having absent (type A) plicae, 14 knees as having a complete septum (type F), and 88 knees were classified as "other." There were no significant relationships between disease type and the morphological characteristics of the plicae (chi-squared test, p = 0.35). Suprapatellar pain was observed in five cases, of which two patients were diagnosed with intra-articular free body, one patient with synovitis combined osteoarthritis, and two patients with suprapatellar plica syndrome with a complete septum. The latter two cases experienced knee symptom resolution soon after arthroscopic resection of the plica. Conclusions: Although the results did not show any relationship between forms of plica remnants and primary disease type, all patients diagnosed with suprapatellar plica syndrome showed complete septum type suprapatellar plicae. A large population study is required in the future. Keywords: Arthroscopy, Knee, Patellofemoral pain syndrome, Suprapatellar plica